Prostate Cancer: A Retrospective Analysis of Prostate Pathology in PUMHS-W Nawabshah and Comparison with Different Cities of Pakistan and Worldwide. - Kousar Parveen , Qamar Raza Brohi2, Muhammad Ali Suhail3, Ameer Hamzo Dahri’, Sikander Ali Sial’, Rabia Shams Qazi.’ (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine the number of malignancies in prostatic biopsies during 06 year period in Nawabshah and comparison of incidence of prostate carcinoma with other cities of Pakistan and worldwide. Material & Method: The study type is Retrospective and duration is 06 years from 2012 to 2017. All the patients data was recorded in the pathology department, biopsies received and processed for histopathological evaluation, diagnosed under microscope following routine Haematoxylin & Eosin stain were included. The details of patients were taken and recorded on proforma and Microsoft Excel and diagnosis was confirmed from computerized record of pathology department PUMHS-W. The records of all patients who had prostate biopsies from January 2012 to December 2017 were reviewed. Pathological data were found for 697 patients of whom 87(12%) were confirmed carcinoma of the prostate. The published articles on prostate cancer and cancer incidence published in Pakistan & worldwide were selected by using google scholar and pub med. The results of all studies were selected and compared with our study. The collected data was analyzed by using SPSS 20. Results: The record of all patients who had prostate biopsies from January 2012 to December 2017 was reviewed. Pathological data were found for 697 whom 87(129c) were confirmed adenocarcinoma prostate. The age ranges of patient were from 40 years to 80 years. Most common age group involved was from 60-69 years of age. Gleason score ranged from 2 to 8 in our study. The highest numbers of patients were seen with Gleason grade 3, 24 (289c). In Pakistan and worldwide the incidence of prostate carcinoma is variable but increased in past. Conclusion:The carcinoma prostate incidence is variable and rising in Pakistan. We found the lower percentage of adenocarcinoma prostate in 40-49 years of age group. The frequency of patients with Gleason score less than7 were 879c and more than 7 were 139c reflects the different trends in Pakistan as compared to other countries of Asia and West World.